The Impact of Compensation and Work Motivation on Job Satisfaction of PT Toraya Cipta Gemilang Production Employees in Mojokerto Regency - Astuti, Nur Habibah Dwi; Kustini, Kustini (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research aims to determine the influence of compensation and work motivation on job satisfaction of production employees of PT. Toraya Cipta Gemilang, Mojokerto Regency. The method used in this research is a quantitative method. Sampling used non-probability sampling techniques using saturated sampling. A saturated sample was used in this study because the entire population was used. The population in this study was 86 people, so the sample used in this study was 86 people. The data analysis technique used in this research uses Partial least squares (PLS). The results of the research show that the independent variable (X1) compensation contributes to the dependent variable job satisfaction (Y) and the independent variable work motivation (X2) contributes to the dependent variable job satisfaction (Y) of production employees of PT. Toraya Cipta Gemilang in Mojokerto Regency. Providing competitive compensation has a direct impact on individual happiness in the organization, greater compensation means happier employees and the provision of motivation carried out by various parties has an impact on employee job satisfaction in the company, thus having a positive impact on the company as well.